Two-dimensional halide perovskite nanomaterials and heterostructures. (22nd March 2018) - Shi, Enzheng; Gao, Yao; Finkenauer, Blake P.; Akriti,; Coffey, Aidan H.; Dou, Letian
Abstract : Novel two-dimensional halide perovskite nanomaterials and heterostructures enable next generation high performance electronics and photonics. Abstract : Over the last several years, there has been tremendous progress in the development of nanoscale halide perovskite materials and devices that possess a wide range of band gaps and tunable optical and electronic properties. Particularly, the emerging two-dimensional (2D) forms of halide perovskites are attracting more interest due to the long charge carrier lifetime, high photoluminescence quantum efficiency, and great defect tolerance. Interfacing 2D halide perovskites with other 2D materials including graphene and transition metal dichalcogenides (TMDs) significantly broadens the application range of the 2D materials and enhances the performance of the functional devices. The synthesis and characterization of 2D halide perovskite nanostructures, the interface of the 2D halide perovskites with other 2D materials, and the integration of them into high-performance optoelectronic devices including solar cells, photodetectors, transistors, and memory devices are currently under investigation. In this article, we review the progress of the above-mentioned topics in a timely manner and discuss the current challenges and future promising directions in this field.